The effect of mortality salience on status consumption among elderly individuals: the moderating role of chronological age and subjective age. Issue 1 (13th December 2021) - Rezaee Vessal, Saeedeh; Partouche-Sebban, Judith
Abstract : Purpose: Over the past two decades, a large body of research has examined the effect of the awareness of the inevitability of death on consumption behaviours. However, the literature has shed little light on the effect of mortality salience (MS) on elderly individuals. The present research specifically aims to challenge the effect of MS on status consumption among elderly individuals. Design/methodology/approach: Two experiments were conducted among individuals over 50. The experiments manipulated MS to test its effect on status consumption. Findings: The results demonstrate that MS positively influences the preference for status products among elderly individuals (experiment 1) and that this effect is less pronounced as elderly individuals age (experiment 2). Subjective age bias, defined as the potential gap between chronological age and subjective age, negatively moderates this effect (experiment 2). Practical implications: Luxury marketers need to pay attention to generational cohorts rather than other demographic variables in the segmentation of their market. Moreover, subjective age may be a better segmentation variable for marketers than objective variables such as chronological age. Originality/value: This research provides insights that support a better understanding of status consumption among elderly individuals and the role of subjective ageing in this process.